Mechanical behavior and recovery of fiber reinforced concrete after high temperature exposure - Akca, Abdullah Huzeyfe. (Thesis (Ph.D.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2017., 2017)
In spite of the importance of strength regain of re damaged concrete in terms of repair and rehabilitation, very few studies had been conducted. Most of the available data are in qualitative form and restricted to strength recovery only. In this study, rehydration and deterioration processes of concrete after high temperature exposure were investigated in details. Therefore, air and water re-curing methods were applied to air entrained ber reinforced concrete incorporating di erent type of cementitious materials. Before and after re-curing processes, compression tests were conducted to determine mechanical properties and SEM, XRD and TG analyses were carried out to determine the morphological changes in concrete. Moreover, heated surfaces of concrete were monitored during air-recuring period and the relation between crack growth rate and compressive strength reduction were investigated. Deterioration in mechanical properties and changes in microstructure of concrete were observed after heating and these deterioration and changes continued during air re-curing period. On the other hand, recovery in mechanical properties and morphology of concrete were observed after water re-curing period. And nally, similar tests were conducted on reinforced concrete beams and prominent e ects of air and water re-curing were also observed in these specimens.
Keywords: Reinforced concrete, Fiber.